Copper-based selenide for microwave absorption, preparation method and application

By using zinc selenide and selective ion exchange reaction at low temperatures, the problems of high energy consumption and poor polarization site controllability in the prior art are solved, and efficient microwave absorption is achieved Material preparation, with broadband absorption and good industrial application potential.

CN119263224APending Publication Date: 2025-01-07XIDIAN UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411449972.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The prior art has problems such as high energy consumption, large cost, complex steps and poor polarization site controllability when preparing microwave absorbing materials, and it is difficult to meet the requirements of wide bandwidth, strong absorption, light weight and thin thickness in the high frequency range.

Method used

Zinc selenide is used as the parent material, and non-stoichiometric copper-based selenide is prepared at a lower temperature in combination with selective ion exchange reaction. By flexibly regulating the degree of ion exchange reaction, a structure with multiple phase composite and rich selenium vacancy defects is formed. Increase the contact area of ​​heterogeneous interfaces and expose active polarization sites.

Benefits of technology

It realizes the preparation of microwave absorbing materials with low energy consumption, low cost and simple processes, with good electromagnetic response and broadband absorption performance, and is suitable for industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119263224A_ABST
    Figure CN119263224A_ABST
Patent Text Reader

Abstract

The invention discloses a copper-based selenide for microwave absorption, a preparation method and application, the copper-based selenide is a compound formed by compounding any two or more of copper selenide (CuSe), non-stoichiometric copper selenide (Cu2-xSe) and zinc selenide (ZnSe), and the structure of the copper-based selenide is a cubic crystal structure, a hexagonal crystal structure or a combination of the cubic crystal structure and the hexagonal crystal structure; the preparation method comprises the following steps: mixing a solution prepared from hydrazine hydrate (N2H4.H2O) / diethylenetriamine / deionized water with a solution prepared from metal zinc salt and sodium selenite (Na2SeO3), carrying out ultrasonic stirring to obtain a metal zinc selenide (ZnSe) precursor solution, carrying out a hydrothermal reaction on the precursor solution, filtering, and drying to obtain the metal zinc selenide (ZnSe) photocatalyst. Dispersing in a deionized water solution, mixing with metal copper salt to obtain a copper-based selenide precursor solution, finally performing hydrothermal reaction on the copper-based selenide precursor solution, naturally cooling, filtering and drying to obtain metal copper-based selenide; the copper-based selenide is applied to a microwave absorbing material; the preparation raw materials are cheap and easy to obtain, the process is simple, repeatability and controllability are high, consumed time is short, and green and environment-friendly effects are achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of functional materials, and in particular to a copper-based selenide for microwave absorption, a preparation method and an application thereof. Background Art

[0002] With the booming development of modern communication technology based on gigahertz electromagnetic waves, in today's intelligent 5G / 6G era, biological organisms and sensitive electronic devices are subject to increasing electromagnetic radiation and interference. In addition, with more and more high-tech applications in the field of national defense and military, stealth technology has become a typical feature of advanced weapon equipment platforms. Therefore, research and development of advanced absorbing materials with wide bandwidth, strong absorption, light weight and thin thickness in the high frequency range (microwave band, 2-18GHz) is a necessary condition for alleviating electromagnetic pollution and improving the stealth capability of weapons and equipment.

[0003] Transition metal chalcogenides (including metal oxides, metal sulfides, metal selenides and alloy materials) are widely used in the fields of light, electricity and heat due to their rich composition elements, adjustable electronic configuration and vacancy level, and fine crystal structure. Among these materials, metal selenides have higher conductivity, and the bond energy of metal-selenium bonds is weaker than that of metal-sulfur bonds, which will be more conducive to the conversion reaction and are expected to become candidates for high-performance absorbing materials. In theory, the electromagnetic loss capacity of absorbing materials strongly depends on the heterogeneous interface structure and ion vacancy level of the material, because they can act as "polarization sites" under high-frequency alternating electromagnetic fields, causing strong dielectric losses to consume a large amount of electromagnetic energy. However, traditional metal selenides often have a limited number of "polarization sites" due to their limited heterogeneous interfaces and defect levels, resulting in poor dielectric response and narrow absorption bandwidth, which seriously hinders their practical application.

[0004] Due to the unique electronic configuration (non-stoichiometric Cu in the crystal structure + / Cu 2+ The dynamic disorder of the configuration) and the abundance of unsaturated atomic sites (special ion vacancies in the hexagonal structure), non-stoichiometric copper selenide (Cu 2-xSe (where 0 < X < 1) often has more potential active sites. However, the commonly used preparation methods for selenides currently include high-temperature annealing, chemical vapor deposition, acid etching, etc. Although these methods are relatively mature, the nanomaterials prepared currently can often only obtain limited lattice vacancies and insufficient heterointerfacial structures, resulting in the inability to fully expose the "polarization sites", which greatly affects the electromagnetic response and broadband absorption ability of the microwave absorption material and cannot meet the application requirements of "thin, wide, strong" and good environmental applicability. In addition, these preparation methods often involve high-temperature treatment, inert gas protection, and multi-step treatment, etc., resulting in the disadvantages of complex and cumbersome preparation processes, high energy consumption, and long cycles for the invention method. At the same time, it also reduces the regulation and optimization of the "polarization sites" and properties of the material during the synthesis process, restricting the large-scale manufacturing and commercial application of the material. Therefore, it is imperative to develop copper-based metal selenides with simple processes, low costs, high "polarization sites", and broadband microwave absorption.

[0005] The Chinese patent application with the publication number CN116332137A discloses a multi-metal selenide microwave absorption material and its preparation method. However, due to the need for atmosphere (nitrogen and / or argon) protection and high-temperature (490 - 600 °C) calcination treatment during the preparation process, it has disadvantages such as high energy consumption and high costs.

[0006] Tianqi Hou et al. disclosed a method for using a metal-organic framework-derived nickel selenide / cobalt selenide@carbon / transition metal carbide composite as an electromagnetic wave absorber (Hou Tianqi et al. Metal-organic framework-derived NiSe2-CoSe2@C / Ti3C2T x composites as electromagnetic wave absorbers[J].Chemical Engineering Journal,2021,422:130079). A selenide-based composite material was prepared using a metal-organic framework as a template through subsequent hydrothermal treatment and high-temperature selenization reaction. However, due to the multi-step process involved in the preparation process and the need for high-temperature (400 °C) selenization treatment, it has disadvantages such as complex steps, poor repeatability, high energy consumption, high costs, and poor controllability of "polarization sites". Summary of the Invention

[0007] In order to overcome the shortcomings of the above-mentioned prior art, the purpose of the present invention is to provide a copper-based selenide for microwave absorption, a preparation method and an application thereof. Zinc selenide (ZnSe) is used as a parent material, and a cheap copper metal salt is used as a copper source. Combined with a subsequent selective ion exchange reaction, a variety of non-stoichiometric copper-based selenide absorbing materials can be prepared at a relatively low temperature, thereby avoiding the shortcomings of the traditional method such as high energy consumption, high cost, complex steps and poor repeatability. In addition, due to the convenience of the ion exchange reaction, the degree of the ion exchange reaction can be selectively regulated by flexibly changing the type and concentration of anions and cations, as well as the reaction temperature and time. The prepared transition metal copper-based selenide presents the characteristics of multi-phase composite and rich selenium vacancy defects, which increases the contact area of ​​the heterogeneous interface, is conducive to the exposure of the active "polarization site", and solves the shortcomings of the traditional method such as the poor controllability of the "polarization site". A large number of "polarization sites" enhance the dielectric response of the material to electromagnetic waves and achieve broadband absorption.

[0008] In order to achieve the above object, the technical solution adopted by the present invention is:

[0009] A copper-based selenide for microwave absorption, wherein the copper-based selenide is copper selenide (CuSe), non-stoichiometric copper selenide (Cu 2-x A composite of any two or more of Se) and zinc selenide (ZnSe), wherein 0 <X<1;

[0010] Copper selenide (CuSe) and non-stoichiometric copper selenide (Cu 2-x Se) composite mass ratio is 2: (1 ~ 5);

[0011] The mass ratio of zinc selenide (ZnSe) and copper selenide (CuSe) is (1-10):1;

[0012] Zinc selenide (ZnSe) and non-stoichiometric copper selenide (Cu 2-x The mass ratio of Se is (1-3):1;

[0013] Zinc selenide (ZnSe), copper selenide (CuSe) and non-stoichiometric copper selenide (Cu 2-x When zinc selenide (ZnSe) and copper selenide (CuSe) are combined, the total mass of copper selenide (CuSe) and the non-stoichiometric ratio of zinc selenide (ZnSe) and copper selenide (CuSe) are 2-x The mass ratio of zinc selenide (ZnSe) to copper selenide (CuSe) is (0.5-3):1, wherein the mass ratio of zinc selenide (ZnSe) to copper selenide (CuSe) is (2-6):1.

[0014] A copper-based selenide for microwave absorption, wherein the zinc selenide (ZnSe) has a cubic crystal structure, the copper selenide (CuSe) has a hexagonal crystal structure, and the non-stoichiometric copper selenide (Cu 2-xSe) has a cubic crystal structure, and when the copper-based selenide is a composite of multiple types, its structure is a combination of a cubic crystal structure and a hexagonal crystal structure.

[0015] A method for preparing a copper-based selenide for microwave absorption comprises the following steps:

[0016] Step 1: Prepare solution A using deionized water as a dispersant: mix hydrated hydrazine (N2H4·H2O), diethyltriamine and deionized water, the volume ratio of hydrated hydrazine (N2H4·H2O), diethyltriamine and deionized water is (1-5):14:16, and stir magnetically at room temperature for 30-60 minutes at a speed of 300-800 r / min to obtain solution A;

[0017] Step 2: Prepare a B solution using deionized water as a dispersant: mix a metal zinc salt and sodium selenite (Na2SeO3) in a mass molar ratio of 1:(1-3) to obtain a B solution; mix the A solution obtained in step 1 with the B solution in a volume ratio of (1-3):1; stir magnetically at room temperature for 5-30 minutes to obtain a mixed solution;

[0018] Step 3: using an ultrasonic cell disruptor to ultrasonically mix and stir the mixed solution obtained in step 2 at room temperature, the power of the ultrasonic cell disruptor is 50-300w, ultrasonication is performed 60-300 times, each ultrasonication is performed for 5-20 seconds, and then stopped for 10-30 seconds. After ultrasonic stirring for 45-90 minutes, the mixture is cooled to room temperature to form a metal zinc selenide (ZnSe) precursor solution;

[0019] Step 4: Transfer the precursor solution obtained in step 3 to a high-pressure reactor, perform a hydrothermal reaction at 120-150° C. for 3-10 hours, cool naturally, filter, dry, and grind to obtain the corresponding metal zinc selenide (ZnSe) powder;

[0020] Step 5: Dispersing the metal zinc selenide (ZnSe) powder obtained in step 4 in a deionized water solution to form a zinc selenide solution with a concentration of 0.1 to 0.5 mmol / mL, then adding 0.05 to 10 mmol / mL of a metal copper salt to the zinc selenide solution, wherein the mass molar ratio of the metal zinc selenide to the metal copper salt is 1:(0.5 to 20), and magnetically stirring the obtained mixed solution at room temperature for 5 to 30 minutes to obtain a copper-based selenide precursor solution;

[0021] Step 6: Transfer the precursor solution obtained in step 5 to a high-pressure reactor, carry out a hydrothermal reaction in a forced air drying oven at 120-160° C. for 0-8 h, cool naturally, filter and dry to obtain the corresponding metallic copper-based selenide, and seal and store for later use.

[0022] In the step 1, the volume ratio of hydrazine hydrate (N2H4·H2O), diethyltriamine and deionized water is preferably 5:14:16, the magnetic stirring time is preferably 60 min, and the magnetic stirring speed is 600 r / min.

[0023] The anion of the metal zinc salt in step 2 is one of chloride, nitrate, acetate and sulfate, preferably zinc acetate (Zn(OAC)2·2H2O);

[0024] In the step 2, the mass molar ratio of the metal zinc salt to the sodium selenite is preferably 1:1, the volume ratio of the A solution to the B solution is preferably 3:1, and the magnetic stirring time is preferably 30 min.

[0025] In step 3, the ultrasonic cell disruptor preferably has a power of 200 W, ultrasonicates 150 times, each ultrasonication lasts for 5 seconds, and stops for 25 seconds, and ultrasonic stirring is performed for 60 minutes.

[0026] The hydrothermal reaction process in step 4 is specifically as follows: in a blast drying oven, the hydrothermal reaction temperature is preferably 150° C., and the reaction time is preferably 8 hours;

[0027] The filtration process in step 4 is specifically as follows: centrifugal washing with deionized water at a speed of 8000-10000 rpm for no less than 3 times; the drying process is preferably carried out in a vacuum drying oven at 60-80° C. for 8-10 hours.

[0028] The concentration of the zinc selenide solution in step 5 is preferably 0.3 mmol / mL;

[0029] The anion of the metal copper salt in step 5 is one of chloride, nitrate, acetate and sulfate, preferably copper nitrate (Cu(NO3)2·3H2O);

[0030] In step 5, the magnetic stirring time is preferably 30 min.

[0031] The hydrothermal reaction temperature in step 6 is preferably 150°C;

[0032] The filtration process in step 6 is specifically as follows: centrifugal washing with deionized water at a speed of 8000-10000 rpm for no less than 3 times; the drying process is preferably carried out in a vacuum drying oven at 60-80° C. for 8-10 hours.

[0033] A copper-based selenide for microwave absorption and an application of a preparation method thereof. The copper-based selenide is applied as a microwave absorption material.

[0034] Compared with the prior art, the beneficial effects of the present invention are:

[0035] 1. Compared with the traditional high-energy consumption high-temperature selenization growth method, the present invention has mild conditions and takes less time.

[0036] 2. The present invention utilizes ion exchange technology to flexibly prepare a variety of copper-based selenides, avoiding the difficulty that the traditional preparation process involves multiple steps and requires high-temperature selenization treatment, and has the effects of simple preparation process, strong repeatability and controllability.

[0037] 3. The raw materials used in the present invention are cheap metal inorganic salts. The raw materials are cheap and easy to obtain, the method is green and environmentally friendly, has the potential for industrialization, and is suitable for actual industrial applications.

[0038] 4. The present invention adopts copper ion concentration control combined with reaction time optimization method to selectively control the degree of ion exchange reaction, and the prepared non-stoichiometric copper-based selenide has the characteristics of multi-phase composite and rich selenium vacancy defects.

[0039] 5. The non-stoichiometric copper-based selenide prepared by the selective ion exchange reaction of the present invention has abundant "polarization sites", controllable component characteristics and adjustable defect concentration, has large reflection loss and absorption bandwidth at low thickness, and can effectively absorb 99.99% of electromagnetic waves.

[0040] In summary, compared with the prior art, the present invention uses metal inorganic salts as raw materials and utilizes selective ion exchange technology of zinc selenide and copper ions to prepare a variety of non-stoichiometric copper-based selenides. The raw materials for preparation are cheap and easy to obtain, the process is simple, the repeatability and controllability are strong, the time consumption is short, and it is green and environmentally friendly. The prepared composite material has the characteristics of multi-phase composite, rich selenium vacancy defects, and wide absorption bandwidth and high absorption intensity of electromagnetic waves. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 is the X-ray diffraction spectrum of the copper-based selenide absorbing material prepared by the present invention, wherein P-0 represents the zinc selenide (ZnSe) absorbing material prepared in the comparative example, P-1:0.5 represents the zinc selenide / copper selenide (ZnSe / CuSe) composite absorbing material prepared in Example 1, and P-1:2 represents the binary copper-based selenide (CuSe / CuSe) composite absorbing material prepared in Example 2. 1.75 Se) composite absorbing material.

[0042] Figure 2 It is a scanning electron microscope image of zinc selenide (ZnSe) prepared in the comparative example of the present invention.

[0043] Figure 3 It is a schematic diagram of reflection loss of zinc selenide (ZnSe) prepared in the comparative example of the present invention.

[0044] Figure 4It is a scanning electron microscope image of the zinc selenide / copper selenide (ZnSe / CuSe) composite absorbing material prepared in Example 1 of the present invention.

[0045] Figure 5 It is a schematic diagram of reflection loss of the zinc selenide / copper selenide (ZnSe / CuSe) composite absorbing material prepared in Example 1 of the present invention.

[0046] Figure 6 The non-stoichiometric binary copper-based selenide (CuSe / Cu 1.75 Se) Scanning electron microscope image of the composite absorbing material.

[0047] Figure 7 The non-stoichiometric binary copper-based selenide (CuSe / Cu 1.75 Se) Schematic diagram of reflection loss of composite absorbing materials.

[0048] Figure 8 (a) is a non-stoichiometric ternary copper-based selenide (ZnSe / CuSe / Cu 1.8 Se) X-ray diffraction pattern of composite absorbing material, Figure 8 (b) is a non-stoichiometric ternary copper-based selenide (ZnSe / CuSe / Cu 1.8 Se) Transmission electron microscope image of composite absorbing material.

[0049] Fig. 9 The non-stoichiometric ternary copper-based selenide (ZnSe / CuSe / Cu 1.8 Se) Schematic diagram of reflection loss of composite absorbing materials. DETAILED DESCRIPTION

[0050] The present invention will be described in detail below in conjunction with the accompanying drawings.

[0051] A copper-based selenide for microwave absorption, wherein the copper-based selenide is copper selenide (CuSe), non-stoichiometric copper selenide (Cu 2-x A composite of any two or more of Se) and zinc selenide (ZnSe), wherein 0 <X<1;

[0052] Copper selenide (CuSe) and non-stoichiometric copper selenide (Cu 2-x Se) composite mass ratio is 2: (1 ~ 5);

[0053] The mass ratio of zinc selenide (ZnSe) and copper selenide (CuSe) is (1-10):1;

[0054] Zinc selenide (ZnSe) and non-stoichiometric copper selenide (Cu2-x The mass ratio of Se is (1-3):1;

[0055] Zinc selenide (ZnSe), copper selenide (CuSe) and non-stoichiometric copper selenide (Cu 2-x When zinc selenide (ZnSe) and copper selenide (CuSe) are combined, the total mass of copper selenide (CuSe) and the non-stoichiometric ratio of zinc selenide (ZnSe) and copper selenide (CuSe) are 2-x The mass ratio of zinc selenide (ZnSe) to copper selenide (CuSe) is (0.5-3):1, wherein the mass ratio of zinc selenide (ZnSe) to copper selenide (CuSe) is (2-6):1.

[0056] A copper-based selenide for microwave absorption, wherein the zinc selenide (ZnSe) has a cubic crystal structure, the copper selenide (CuSe) has a hexagonal crystal structure, and the non-stoichiometric copper selenide (Cu 2-x Se) has a cubic crystal structure, and when the copper-based selenide is a composite of multiple types, its structure is a combination of a cubic crystal structure and a hexagonal crystal structure.

[0057] A method for preparing a copper-based selenide for microwave absorption comprises the following steps:

[0058] Step 1: Prepare solution A using deionized water as a dispersant: mix hydrated hydrazine (N2H4·H2O), diethyltriamine and deionized water, the volume ratio of hydrated hydrazine (N2H4·H2O), diethyltriamine and deionized water is (1-5):14:16, and stir magnetically at room temperature for 30-60 minutes at a speed of 300-800 r / min to obtain solution A;

[0059] Step 2: Prepare a B solution using deionized water as a dispersant: mix a metal zinc salt and sodium selenite (Na2SeO3) in a mass molar ratio of 1:(1-3) to obtain a B solution; mix the A solution obtained in step 1 with the B solution in a volume ratio of (1-3):1; stir magnetically at room temperature for 5-30 minutes to obtain a mixed solution;

[0060] Step 3: using an ultrasonic cell disruptor to ultrasonically mix and stir the mixed solution obtained in step 2 at room temperature, the power of the ultrasonic cell disruptor is 50-300w, ultrasonication is performed 60-300 times, each ultrasonication is performed for 5-20 seconds, and then stopped for 10-30 seconds. After ultrasonic stirring for 45-90 minutes, the mixture is cooled to room temperature to form a metal zinc selenide (ZnSe) precursor solution;

[0061] Step 4: Transfer the precursor solution obtained in step 3 to a high-pressure reactor, perform a hydrothermal reaction at 120-150° C. for 3-10 hours, cool naturally, filter, dry, and grind to obtain the corresponding metal zinc selenide (ZnSe) powder;

[0062] Step 5: Dispersing the metal zinc selenide (ZnSe) powder obtained in step 4 in a deionized water solution to form a zinc selenide solution with a concentration of 0.1 to 0.5 mmol / mL, then adding 0.05 to 10 mmol / mL of a metal copper salt to the zinc selenide solution, wherein the mass molar ratio of the metal zinc selenide to the metal copper salt is 1:(0.5 to 20), and magnetically stirring the obtained mixed solution at room temperature for 5 to 30 minutes to obtain a copper-based selenide precursor solution;

[0063] Step 6: Transfer the precursor solution obtained in step 5 to a high-pressure reactor, carry out a hydrothermal reaction in a forced air drying oven at 120-160° C. for 0-8 h, cool naturally, filter and dry to obtain the corresponding metallic copper-based selenide, and seal and store for later use.

[0064] In the step 1, the volume ratio of hydrazine hydrate (N2H4·H2O), diethyltriamine and deionized water is preferably 5:14:16, the magnetic stirring time is preferably 60 min, and the magnetic stirring speed is 600 r / min.

[0065] The anion of the metal zinc salt in step 2 is one of chloride, nitrate, acetate and sulfate, preferably zinc acetate (Zn(OAC)2·2H2O).

[0066] In the step 2, the mass molar ratio of the metal zinc salt to sodium selenite is preferably 1:1, and the volume ratio of solution A to solution B is preferably 3:1, so as to ensure the strong reducing property of hydrazine hydrate, thereby providing conditions for the subsequent generation of metal zinc selenide (ZnSe) precursor, and the magnetic stirring time is preferably 30 min.

[0067] In the step 3, the ultrasonic cell disruptor preferably has a power of 200 W, and ultrasonication is performed 150 times, with each ultrasonication lasting 5 seconds and a rest period of 25 seconds, and ultrasonic stirring is performed for 60 minutes to avoid the generation of bubbles, thereby forming a uniformly mixed metal zinc selenide (ZnSe) precursor solution.

[0068] The hydrothermal reaction process in step 4 is specifically as follows: in a blast drying oven, the hydrothermal reaction temperature is preferably 150° C., and the reaction time is preferably 8 hours;

[0069] The filtration process in step 4 is specifically as follows: centrifugal washing with deionized water at a speed of 8000-10000 rpm for no less than 3 times; the drying process is preferably carried out in a vacuum drying oven at 60-80° C. for 8-10 hours.

[0070] The concentration of the zinc selenide solution in step 5 is preferably 0.3 mmol / mL, which can promote different degrees of selective cation exchange between metal zinc ions and metal copper ions, and also promote different degrees of selective anion exchange between non-metallic selenium ions and non-metallic cations, which is ultimately beneficial for the prepared metal copper-based selenide to present the advantages of multi-phase composite and rich selenium vacancy defects, thereby facilitating the subsequent optimization of the electromagnetic parameters of the material and improving the electromagnetic wave absorption performance of the material;

[0071] The anion of the metal copper salt in step 5 is one of chloride, nitrate, acetate and sulfate, preferably copper nitrate (Cu(NO3)2·3H2O);

[0072] In step 5, the magnetic stirring time is preferably 30 min.

[0073] The hydrothermal reaction temperature in step 6 is preferably 150° C., so that the phase composition, stoichiometric ratio and lattice defect level of the metallic copper-based selenide can be further optimized from a thermodynamic perspective through different reaction times, and ultimately a non-stoichiometric copper-based selenide with a high “polarization site” is prepared to enhance the dielectric response of the material to electromagnetic waves.

[0074] The filtration process in step 6 is specifically as follows: centrifugal washing with deionized water at a speed of 8000-10000 rpm for no less than 3 times; the drying process is preferably carried out in a vacuum drying oven at 60-80° C. for 8-10 hours.

[0075] The copper-based selenide is used as a microwave absorbing material.

[0076] Comparative Example

[0077] A method for preparing a zinc selenide (ZnSe) absorbing material comprises the following steps:

[0078] Step 1: Prepare solution A using deionized water as a dispersant: mix hydrated hydrazine (N2H4·H2O), diethyltriamine, and deionized water in a volume ratio of 5:14:16, and stir magnetically at room temperature for 60 min at a speed of 600 r / min to obtain solution A;

[0079] Step 2: Prepare solution B using deionized water as a dispersant: Mix zinc acetate (Zn(OAC)2·2H2O) and sodium selenite (Na2SeO3) in a mass molar ratio of 1:1 to obtain solution B. Mix solution A obtained in step 1 with the above solution B in a volume ratio of 3:1, and stir magnetically at room temperature for 30 minutes to obtain a mixed solution.

[0080] Step 3: using an ultrasonic cell disruptor to ultrasonically mix and stir the mixed solution obtained in step 2 at room temperature, the power of the ultrasonic cell disruptor is 200 W, ultrasonication is performed 150 times, each ultrasonication is performed for 5 seconds, and then stopped for 25 seconds. After ultrasonic stirring for 60 minutes, it is cooled to room temperature to form a metal zinc selenide (ZnSe) precursor solution;

[0081] Step 4: Transfer the precursor solution obtained in step 3 to a high-pressure reactor, perform a hydrothermal reaction in a forced air drying oven at 150°C for 8 hours, cool naturally, wash three times by centrifugation at 8000 rpm with deionized water, and place in a vacuum drying oven at 80°C for 8 hours to obtain the corresponding metal zinc selenide (ZnSe), abbreviated as P-0.

[0082] Figure 1 In the figure, P-0 is the X-ray diffraction spectrum of the zinc selenide (ZnSe) absorbing material prepared in the comparative example of the present invention. The main peak is the peak of zinc selenide (ZnSe), which has a good peak shape and good crystallinity. Figure 2 The SEM image of zinc selenide (ZnSe) prepared in the comparative example shows that it is in the shape of a ribbon and is self-assembled by a large number of nanoparticles. Figure 3 It can be seen that the wave absorbing performance of the comparative example of the present invention is poor and still needs to be further improved.

[0083] Example 1

[0084] A copper-based selenide for microwave absorption includes zinc selenide (ZnSe) and copper selenide (CuSe), wherein the weight ratio of zinc selenide (ZnSe) to copper selenide (CuSe) is 6:1.

[0085] A copper-based selenide for microwave absorption includes two types: zinc selenide (ZnSe) with a cubic crystal structure and copper selenide (CuSe) with a hexagonal crystal structure.

[0086] A method for preparing a zinc selenide / copper selenide (ZnSe / CuSe) composite absorbing material comprises the following steps:

[0087] Step 1: Prepare solution A using deionized water as a dispersant: mix hydrated hydrazine (N2H4·H2O), diethyltriamine, and deionized water, wherein the volume ratio of hydrated hydrazine (N2H4·H2O), diethyltriamine, and deionized water is 5:14:16, and the obtained solution is magnetically stirred at room temperature for 60 minutes at a speed of 600 r / min to obtain solution A;

[0088] Step 2: Prepare solution B using deionized water as a dispersant: mix zinc acetate (Zn(OAC)2·2H2O) and sodium selenite (Na2SeO3) in a mass molar ratio of 1:1 to obtain solution B; mix solution A obtained in step 1 with the above solution B in a volume ratio of 3:1; and stir magnetically at room temperature for 30 minutes to obtain a mixed solution;

[0089] Step 3: using an ultrasonic cell disruptor to ultrasonically mix and stir the mixed solution obtained in step 2 at room temperature, the power of the ultrasonic cell disruptor is 200 W, ultrasonication is performed 150 times, each ultrasonication is performed for 5 seconds, and then stopped for 25 seconds. After ultrasonic stirring for 60 minutes, it is cooled to room temperature to form a metal zinc selenide (ZnSe) precursor solution;

[0090] Step 4: The precursor solution obtained in step 3 is transferred to a high-pressure reactor, and the hydrothermal reaction is kept at 150°C for 8 hours in a forced air drying oven, and then naturally cooled. After centrifugal washing with deionized water at 8000 rpm for 3 times, it is placed in a vacuum drying oven and kept at 80°C for 8 hours, and ground to obtain the corresponding metal zinc selenide (ZnSe) powder, abbreviated as P-0.

[0091] Step 5: Disperse the metal zinc selenide (ZnSe) powder obtained in step 4 in a deionized water solution to form a zinc selenide solution with a concentration of 0.1 mmol / mL, then add 0.05 mmol / mL of metal copper salt to the zinc selenide solution, wherein the mass molar ratio of metal zinc selenide to metal copper salt is 1:0.5, and the obtained mixed solution is magnetically stirred at room temperature for 30 minutes to obtain a copper-based selenide precursor solution;

[0092] Step 6: The precursor solution obtained in step 5 is transferred to a high-pressure reactor, and the hydrothermal reaction is kept warm for 8 hours at 150°C in a forced air drying oven, and then naturally cooled. After centrifugal washing at 8000 rpm with deionized water for 3 times, the solution is kept warm at 80°C in a vacuum drying oven for 8 hours to obtain the corresponding zinc selenide / copper selenide (ZnSe / CuSe) composite absorbing material, abbreviated as P-1:0.5, which is sealed and stored for later use.

[0093] Figure 1 In the figure, P-1:0.5 is the X-ray diffraction spectrum of the prepared sample zinc selenide / copper selenide (ZnSe / CuSe) composite absorbing material. Compared with the comparative example P-0, in addition to the peak of zinc selenide (ZnSe), a small amount of copper selenide peak (CuSe) also appeared. This shows that increasing the copper ion concentration promotes the occurrence of partial cation exchange reaction between zinc ions in the parent ZnSe and copper ions in the solution, thereby in-situ loading and generating a small amount of copper selenide (CuSe) on the parent ZnSe. Figure 4This is a scanning electron microscope image of the zinc selenide / copper selenide (ZnSe / CuSe) composite absorbing material (P-1:0.5) prepared in Example 1 of the present invention. It can be seen that its morphology is "broccoli"-like, and the surface is self-assembled by a large number of nanoparticles. The reflection loss schematic diagram of the zinc selenide / copper selenide (ZnSe / CuSe) composite absorbing material (P-1:0.5) prepared in Example 1 is shown in FIG. Figure 5 , its wave absorbing performance is greatly improved compared with the comparative example (P-0) of the present invention. This indicates that the formation of numerous zinc selenide / copper selenide (ZnSe / CuSe) heterogeneous interfaces leads to a significant reduction in the incident electromagnetic wave due to polarization loss, and finally achieves good wave absorbing performance.

[0094] The zinc selenide / copper selenide (ZnSe / CuSe) composite wave absorbing material is used as an electromagnetic wave absorbing material.

[0095] Example 2

[0096] A non-stoichiometric copper-based selenide for microwave absorption, comprising copper selenide (CuSe) and non-stoichiometric copper selenide (Cu 1.75 The copper selenide (CuSe) and the non-stoichiometric copper selenide (Cu 1.75 Se) by weight ratio is 1:1.

[0097] A non-stoichiometric copper-based selenide for microwave absorption, comprising hexagonal crystal structure copper selenide (CuSe) and cubic crystal structure non-stoichiometric copper selenide (Cu 1.75 Se) two types.

[0098] A non-stoichiometric binary copper-based selenide (CuSe / Cu 1.75 Se) A method for preparing a composite wave absorbing material, comprising the following steps:

[0099] Step 1: Prepare solution A using deionized water as a dispersant: mix hydrated hydrazine (N2H4·H2O), diethyltriamine, and deionized water in a volume ratio of 5:14:16, and stir magnetically at room temperature for 60 minutes at a speed of 600 r / min to obtain solution A;

[0100] Step 2: Prepare solution B using deionized water as a dispersant: mix zinc acetate (Zn(OAC)2·2H2O) and sodium selenite (Na2SeO3) in a mass molar ratio of 1:1 to obtain solution B, and mix solution A obtained in step 1 with the above solution B in a volume ratio of 3:1; the obtained solution is magnetically stirred at room temperature for 30 minutes to obtain a mixed solution;

[0101] Step 3: using an ultrasonic cell disruptor to ultrasonically mix and stir the mixed solution obtained in step 2 at room temperature, the power of the ultrasonic cell disruptor is 200 W, ultrasonication is performed 150 times, each ultrasonication is performed for 5 seconds, and then stopped for 25 seconds. After ultrasonic stirring for 60 minutes, it is cooled to room temperature to form a metal zinc selenide (ZnSe) precursor solution;

[0102] Step 4: The precursor solution obtained in step 3 is transferred to a high-pressure reactor, and the hydrothermal reaction is kept at 150°C for 8 hours in a forced air drying oven, and then naturally cooled. After centrifugal washing with deionized water at 8000 rpm for 3 times, it is placed in a vacuum drying oven and kept at 80°C for 8 hours, and ground to obtain the corresponding metal zinc selenide (ZnSe) powder, abbreviated as P-0.

[0103] Step 5: Disperse the metal zinc selenide (ZnSe) powder obtained in step 4 in a deionized water solution to form a zinc selenide solution with a concentration of 0.2 mmol / mL, then add 0.4 mmol / mL of metal copper salt to the zinc selenide solution, wherein the mass molar ratio of metal zinc selenide to metal copper salt is 1:2, and the obtained mixed solution is magnetically stirred at room temperature for 30 minutes to obtain a copper-based selenide precursor solution;

[0104] Step 6: The precursor solution obtained in step 5 was transferred to a high-pressure reactor, and the hydrothermal reaction was kept at 150°C in a forced air drying oven for 8 hours, and then naturally cooled. After centrifugal washing with deionized water at 8000 rpm for 3 times, the precursor solution was kept at 80°C in a vacuum drying oven for 8 hours to obtain the corresponding non-stoichiometric binary copper-based selenide (CuSe / Cu 1.75 Se) composite absorbing material, abbreviated as P-1:2, is sealed and stored for future use.

[0105] Figure 1 In the above example, P-1:2 is the non-stoichiometric ratio of the prepared sample, binary copper-based selenide (CuSe / Cu 1.75 Similarly, compared with P-0 and P-1:0.5, the peak of the parent zinc selenide (ZnSe) disappears, the peak of copper selenide (CuSe) still exists, and a small amount of non-stoichiometric copper selenide peaks (Cu 1.75 This indicates that further increasing the copper ion concentration promotes the complete cation exchange reaction between the zinc ions in the parent ZnSe and the copper ions in the solution, thereby completely consuming the parent ZnSe and generating copper selenide (CuSe) and non-stoichiometric copper selenide (CuSe) in situ. 1.75 Se). Figure 6 The non-stoichiometric binary copper-based selenide (CuSe / Cu 1.75The scanning electron microscope and transmission electron microscope images of the composite absorber (P-1:2) of the copper-based selenide (CuSe / CuSe) composite absorber (P-1:2) show that its morphology is smooth and "bone-like" and is self-assembled by a large number of nanoparticles. 1.75 Se) The reflection loss diagram of the composite absorbing material (P-1:2) is shown in Figure 7 , its absorption performance is further improved compared with P-0 and P-1:0.5 of the present invention. This shows that many CuSe / Cu 1.75 The formation of Se heterogeneous interface leads to a significant attenuation of the incident electromagnetic wave due to polarization loss. 1.75 The generation of Se) is conducive to bringing more defect sites and enhancing the defect-related dipole polarization. With the joint promotion of interface polarization and dipole polarization, good microwave absorption performance is finally achieved.

[0106] The non-stoichiometric binary copper-based selenide (CuSe / Cu 1.75 Se) composite absorbing materials are used for electromagnetic wave absorbing materials.

[0107] Example 3

[0108] A non-stoichiometric copper-based selenide for microwave absorption, comprising zinc selenide (ZnSe), copper selenide (CuSe) and non-stoichiometric copper selenide (Cu 1.8 The weight ratio of zinc selenide (ZnSe) to copper selenide (CuSe) is 2:1, and the total weight of zinc selenide (ZnSe) and copper selenide (CuSe) is 2:1. 1.8 Se) by weight ratio is 0.5:1.

[0109] A non-stoichiometric copper-based selenide for microwave absorption, comprising cubic crystal structure zinc selenide (ZnSe), hexagonal crystal structure copper selenide (CuSe) and cubic crystal structure non-stoichiometric copper selenide (Cu 1.8 Se) three types, of which 0 <X<1。

[0110] A non-stoichiometric ternary copper-based selenide (ZnSe / CuSe / Cu 1.8 Se) A method for preparing a composite wave absorbing material, comprising the following steps:

[0111] Step 1: Prepare solution A using deionized water as a dispersant: mix hydrated hydrazine (N2H4·H2O), diethyltriamine, and deionized water in a volume ratio of 5:14:16, and stir magnetically at room temperature for 60 minutes at a speed of 600 r / min to obtain solution A;

[0112] Step 2: Prepare solution B using deionized water as a dispersant: mix zinc acetate (Zn(OAC)2·2H2O) and sodium selenite (Na2SeO3) in a mass molar ratio of 1:1 to obtain solution B, and mix solution A obtained in step 1 with the above solution B in a volume ratio of 3:1; stir magnetically at room temperature for 30 minutes to obtain a mixed solution;

[0113] Step 3: using an ultrasonic cell disruptor to ultrasonically mix and stir the mixed solution obtained in step 2 at room temperature, the power of the ultrasonic cell disruptor is 200 W, ultrasonication is performed 150 times, each ultrasonication is performed for 5 seconds, and then stopped for 25 seconds. After ultrasonic stirring for 60 minutes, it is cooled to room temperature to form a metal zinc selenide (ZnSe) precursor solution;

[0114] Step 4: The precursor solution obtained in step 3 is transferred to a high-pressure reactor, and the hydrothermal reaction is kept at 150°C for 8 hours in a forced air drying oven, and then naturally cooled. After centrifugal washing with deionized water at 8000 rpm for 3 times, it is placed in a vacuum drying oven and kept at 80°C for 8 hours, and ground to obtain the corresponding metal zinc selenide (ZnSe) powder, abbreviated as P-0.

[0115] Step 5: Disperse the metal zinc selenide (ZnSe) powder obtained in step 4 in a deionized water solution to form a zinc selenide solution with a concentration of 0.3 mmol / mL, then add 0.6 mmol / mL of metal copper salt to the zinc selenide solution, wherein the mass molar ratio of metal zinc selenide to metal copper salt is 1:2, and the obtained mixed solution is magnetically stirred at room temperature for 30 minutes to obtain a copper-based selenide precursor solution;

[0116] Step 6: The precursor solution obtained in step 5 was transferred to a high-pressure reactor, and the hydrothermal reaction was kept at 150°C in a forced air drying oven for 0.5 h, and then naturally cooled. After centrifugal washing with deionized water at 8000 rpm for 3 times, the precursor solution was kept at 80°C in a vacuum drying oven for 8 h to obtain the corresponding non-stoichiometric ternary copper-based selenide (ZnSe / CuSe / Cu 1.8 Se) composite absorbing material, abbreviated as T-0.5, is sealed and stored for future use.

[0117] Figure 8 T-0.5 in (a) is the non-stoichiometric ratio of the prepared sample ternary copper-based selenide (ZnSe / CuSe / Cu 1.8 X-ray diffraction spectrum of the composite absorber material with a ratio of 1:2:1. Compared with P-1:2, the peak of the parent zinc selenide (ZnSe) has not disappeared, the peak of copper selenide (CuSe) still exists, and the peak of non-stoichiometric copper selenide (CuSe) also appears. 1.8This indicates that further shortening the reaction time from 8 h to 0.5 h promoted the partial cation exchange reaction between the zinc ions in the matrix ZnSe and the copper ions in the solution, and also accelerated the reaction of the divalent copper ions (Cu 2+ ) to monovalent copper ions (Cu + ) transformation. Then, while retaining part of the parent ZnSe, copper selenide (CuSe) and non-stoichiometric copper selenide (Cu 1.8 Se). Figure 8 (b) is a non-stoichiometric ternary copper-based selenide (ZnSe / CuSe / Cu) prepared in Example 3 of the present invention. 1.8 The transmission electron microscope image of the composite absorber (T-0.5) of ZnSe / CuSe / CuSe shows that its morphology is nanoflower-like and is self-assembled from a large number of nanosheets. 1.8 Se) Reflection loss diagram of composite absorbing material (T-0.5) is shown in Fig. 9 Compared with P-0, P-1:0.5 and P-1:2 of the present invention, its wave absorption performance is further improved. This shows that many heterogeneous interfaces (including CuSe / Cu 1.8 Se, ZnSe / Cu 1.8 Se and ZnSe / CuSe) causes the incident electromagnetic wave to be greatly weakened due to polarization loss, and the effective absorption bandwidth increases from 0 to 6.90GHz. 1.8 The coexistence of Se) brings more defect sites, greatly enhancing the defect-related dipole polarization. Under the joint promotion of interface polarization and dipole polarization, the minimum reflection loss value is -52.56dB, which can effectively absorb 99.99% of electromagnetic waves and achieve excellent absorbing performance.

[0118] Through Matlab software simulation, the ternary copper-based selenide (ZnSe / CuSe / Cu 1.8 The minimum reflection loss value of Se) composite absorbing material is -52.56dB, and the effective absorption bandwidth reaches 6.90GHz. It has large reflection loss and absorption bandwidth and can effectively absorb 99.99% of electromagnetic waves.

[0119] The non-stoichiometric ternary copper-based selenide (ZnSe / CuSe / Cu 1.8 Se) composite absorbing materials are used to prepare electromagnetic wave absorbing materials.

Claims

1. A copper-based selenide for microwave absorption, characterized in that: The copper-based selenide is copper selenide (CuSe), non-stoichiometric copper selenide (Cu 2-x A composite of any two or more of Se) and zinc selenide (ZnSe), wherein 0 <X<1; Copper selenide (CuSe) and non-stoichiometric copper selenide (Cu 2-x Se) composite mass ratio is 2: (1 ~ 5); The mass ratio of zinc selenide (ZnSe) and copper selenide (CuSe) is (1-10):1; Zinc selenide (ZnSe) and non-stoichiometric copper selenide (Cu 2-x The mass ratio of Se is (1-3):1; Zinc selenide (ZnSe), copper selenide (CuSe) and non-stoichiometric copper selenide (Cu 2-x When zinc selenide (ZnSe) and copper selenide (CuSe) are combined, the total mass of copper selenide (CuSe) and the non-stoichiometric ratio of zinc selenide (ZnSe) and copper selenide (CuSe) are 2-x The mass ratio of zinc selenide (ZnSe) to copper selenide (CuSe) is (0.5-3):1, wherein the mass ratio of zinc selenide (ZnSe) to copper selenide (CuSe) is (2-6):

1.

2. A copper-based selenide for microwave absorption according to claim 1, characterized in that: The zinc selenide (ZnSe) has a cubic crystal structure, the copper selenide (CuSe) has a hexagonal crystal structure, and the non-stoichiometric copper selenide (Cu 2-x Se) has a cubic crystal structure, and when the copper-based selenide is a composite of multiple types, its structure is a combination of a cubic crystal structure and a hexagonal crystal structure.

3. A method for preparing a copper-based selenide for microwave absorption according to claim 2, characterized in that: The following steps are involved: Step 1: Prepare solution A using deionized water as a dispersant: mix hydrated hydrazine (N2H4·H2O), diethyltriamine and deionized water, the volume ratio of hydrated hydrazine (N2H4·H2O), diethyltriamine and deionized water is (1-5):14:16, and stir magnetically at room temperature for 30-60 minutes at a speed of 300-800 r / min to obtain solution A; Step 2: Prepare a B solution using deionized water as a dispersant: mix a metal zinc salt and sodium selenite (Na2SeO3) in a mass molar ratio of 1:(1-3) to obtain a B solution; mix the A solution obtained in step 1 with the B solution in a volume ratio of (1-3):1; stir magnetically at room temperature for 5-30 minutes to obtain a mixed solution; Step 3: using an ultrasonic cell disruptor to ultrasonically mix and stir the mixed solution obtained in step 2 at room temperature, the power of the ultrasonic cell disruptor is 50-300w, ultrasonication is performed 60-300 times, each ultrasonication is performed for 5-20 seconds, and then stopped for 10-30 seconds. After ultrasonic stirring for 45-90 minutes, the mixture is cooled to room temperature to form a metal zinc selenide (ZnSe) precursor solution; Step 4: Transfer the precursor solution obtained in step 3 to a high-pressure reactor, perform a hydrothermal reaction at 120-150° C. for 3-10 hours, cool naturally, filter, dry, and grind to obtain the corresponding metal zinc selenide (ZnSe) powder; Step 5: Dispersing the metal zinc selenide (ZnSe) powder obtained in step 4 in a deionized water solution to form a zinc selenide solution with a concentration of 0.1 to 0.5 mmol / mL, then adding 0.05 to 10 mmol / mL of a metal copper salt to the zinc selenide solution, wherein the mass molar ratio of the metal zinc selenide to the metal copper salt is 1:(0.5 to 20), and magnetically stirring the obtained mixed solution at room temperature for 5 to 30 minutes to obtain a copper-based selenide precursor solution; Step 6: Transfer the precursor solution obtained in step 5 to a high-pressure reactor, carry out a hydrothermal reaction in a forced air drying oven at 120-160° C. for 0-8 h, cool naturally, filter and dry to obtain the corresponding metallic copper-based selenide, and seal and store for later use.

4. The method for preparing a copper-based selenide for microwave absorption according to claim 3, characterized in that: In the step 1, the volume ratio of hydrazine hydrate (N2H4·H2O), diethyltriamine and deionized water is preferably 5:14:16, the magnetic stirring time is preferably 60 min, and the magnetic stirring speed is 600 r / min.

5. The method for preparing a copper-based selenide for microwave absorption according to claim 3, characterized in that: The anion of the metal zinc salt in step 2 is one of chloride, nitrate, acetate and sulfate, preferably zinc acetate (Zn(OAC)2·2H2O); In the step 2, the mass molar ratio of the metal zinc salt to the sodium selenite is preferably 1:1, the volume ratio of the A solution to the B solution is preferably 3:1, and the magnetic stirring time is preferably 30 min.

6. The method for preparing a copper-based selenide for microwave absorption according to claim 3, characterized in that: In step 3, the ultrasonic cell disruptor preferably has a power of 200 W, ultrasonicates 150 times, each ultrasonication lasts for 5 seconds, and stops for 25 seconds, and ultrasonic stirring is performed for 60 minutes.

7. The method for preparing a copper-based selenide for microwave absorption according to claim 3, characterized in that: The hydrothermal reaction process in step 4 is specifically as follows: in a blast drying oven, the hydrothermal reaction temperature is preferably 150° C., and the reaction time is preferably 8 hours; The filtration process in step 4 is specifically as follows: centrifugal washing with deionized water at a speed of 8000-10000 rpm for no less than 3 times; the drying process is preferably carried out in a vacuum drying oven at 60-80° C. for 8-10 hours.

8. The method for preparing a copper-based selenide for microwave absorption according to claim 3, characterized in that: The concentration of the zinc selenide solution in step 5 is preferably 0.3 mmol / mL; The anion of the metal copper salt in step 5 is one of chloride, nitrate, acetate and sulfate, preferably copper nitrate (Cu(NO3)2·3H2O); In step 5, the magnetic stirring time is preferably 30 min.

9. The method for preparing a copper-based selenide for microwave absorption according to claim 3, characterized in that: The hydrothermal reaction temperature in step 6 is preferably 150°C; The filtration process in step 6 is specifically as follows: centrifugal washing with deionized water at a speed of 8000-10000 rpm for no less than 3 times; the drying process is preferably carried out in a vacuum drying oven at 60-80° C. for 8-10 hours.

10. The use of a copper-based selenide for microwave absorption and a preparation method according to any one of claims 1 to 9, characterized in that: The copper-based selenide is used as a microwave absorbing material.

Citation Information

Patent Citations

  • Multi-element metal selenide wave-absorbing material and preparation method thereof

    CN116332137A